(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Medical students are particularly vulnerable to psychological distress and sleep disturbances, yet the physiological mechanisms underlying these conditions remain insufficiently understood. Autonomic nervous system dysregulation represents a biologically plausible pathway linking stress to impaired sleep, with implications for student well-being and sustainable health promotion. The objective of this study was to examine the association between autonomic nervous system dysregulation and sleep quality among medical students and to determine whether this relationship is mediated by psychological distress. Methods: In this cross-sectional study, medical students aged 18–25 years underwent an objective assessment of autonomic nervous system function using resting heart rate variability and subjective evaluation via the Composite Autonomic Symptom Score-31 questionnaire. Psychological distress was measured using the Depression Anxiety Stress Scale-21, and sleep quality using the Pittsburgh Sleep Quality Index. Multivariable regression and mediation analyses were performed. Results: Among 312 students, 63.5% had poor sleep quality and 38.8% reported moderate-to-severe psychological distress. Psychological distress was moderately correlated with sleep disturbance (r=0.58). Mediation analysis showed that psychological distress partially mediated the association between reduced root mean square of successive differences and sleep quality, accounting for 41% of the total effect (β=−0.16, 95% confidence interval: –0.25 to −0.09). Conclusion: Targeting autonomic regulation may offer novel intervention pathways to improve mental health and sleep quality among medical students.